Case Studies on Sustainability Factors for Industrialised Building System (IBS) - Riduan Yunus,; Handan, Rabitah; Mehdi Riazi, Salman Riazi (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper presents the outcomes of a case study to test the ability of the Guidelines for Sustainable Construction of Industrialized Building System (GSCIBS). An assessment on the implementation of IBS related guidelines in real projects contributes towards the improvement of these guidelines and ensure the significance of the decision tools in promoting sustainability. In addition, the process involved when using the GSCIBS also demonstrated how the guidelines can be used to assist designers when making a selection with regard to sustainability. Three case projects were selected based on their characteristics (location, accessibility of information, building construction, IBS project with high impact to community and high percentage IBS Score). The projects were categorized as non-residential buildings. Semi-structured interviews and documents’ review were conducted to gather information from the respondents. In total, there are eleven (11) respondents who participated in the case study analysis. The confirmation by the industry participants shows that the guidelines are applicable and suitable to be used in Malaysia. The literal replication was achieved and provides strong evidence that the number of case studies is appropriate. The participants’ comments and suggestions were taken into account in synthesising the project outputs. As a result, the GSCIBS are significant in improving sustainable deliverables of IBS application.